Binary Logistic Regression Analysis of Filing Behavior of the Value-Added Taxpayers in Nepal - Koirala, Kamal Bahadur (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
The main purpose of this research was to assess the differences in Value-Added Tax (VAT) return filing behavior of Nepalese taxpayers as per their gender, geographic location, and business sector. The study is empirical research. Cross-sectional research design was used with quantitative, non-experimental approach using binary logistic regression to study the relationships between independent variables and a binary outcome, like filing behavior of taxpayers. The results showed that male taxpayers have a higher probability than female taxpayers of filing VAT returns on time. Kathmandu Valley-based taxpayers were found less eager to file on time than those outside the valley. Service-based taxpayers, and those in manufacturing and trade across Nepal, had a high probability of timely VAT filing.This research first-time uses binary logistic regression to analyze VAT filing behavior of taxpayers based on their gender, locations, and business sectors in Nepal.Its crucial findings that male taxpayers, those outside Kathmandu Valley, and service, manufacturing, and trade sectors being on-time filers help tax authorities impose legal enforcement to boost compliance, especially among female and taxpayers inside Kathmandu Valley. This research suggests drafting VAT policies that improve the VAT filing process by concentrating on important taxpayers’ behavioral factors which make them not comply, based on unique socio- economic landscape of Nepal.